Design of a well-defined poly(dimethylsiloxane)-based microbial nanoculture system. (June 2021) - Usman, Huda; Davidson, Shanna-Leigh; Manimaran, Nithil H.; Nguyen, Jenna T.; Bah, Aïssatou; Seth, Rishabh; Beckman, Eric; Niepa, Tagbo H.R.
Graphical abstract: Abstract: Organosilanes contain hydrocarbon-like backbones, allowing them to react with silicone-based agents in the presence of a catalyst and polymerize into membranes with tunable transport and mechanical properties. Owing to their hydrophobicity, Poly(dimethylsiloxane) (PDMS) membranes, and more particularly, Sylgard™ 184, have been used for applications including drug delivery, gas separation, and microfluidics fabrication. However, the complex composition of the material and its ability to leach out uncured oligomers make its functionalization and usage challenging for many biological applications. This article presents the design of a novel culture system generated using vinyl-terminated PDMS and Methylhydromethylsiloxanes-Dimethylsiloxane copolymers as the sole building blocks of the shell membrane. The nanoliter microbial culture system that is referred to as "nanoculture" serves to grow and study the dynamics of microbes encapsulated in semipermeable membranes. The mechanical properties of the membranes are investigated to determine the ability of the nanocultures to withstand high shear stress while maintaining transport properties essential to microbial communication and growth. The present study lays the foundation for a novel microbial culture system that could be functionalized on-demand to achieve the cultivation of microorganisms in environments other than laboratory conditions.